2016
DOI: 10.1073/pnas.1517551113
|View full text |Cite
|
Sign up to set email alerts
|

Protein networks identify novel symbiogenetic genes resulting from plastid endosymbiosis

Abstract: The integration of foreign genetic information is central to the evolution of eukaryotes, as has been demonstrated for the origin of the Calvin cycle and of the heme and carotenoid biosynthesis pathways in algae and plants. For photosynthetic lineages, this coordination involved three genomes of divergent phylogenetic origins (the nucleus, plastid, and mitochondrion). Major hurdles overcome by the ancestor of these lineages were harnessing the oxygen-evolving organelle, optimizing the use of light, and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Thus, the chimeric origins of the ochrophyte plastid might have enabled the creation of syncretic proteins not found in the endosymbiont or host ancestors. We identified orthologues of seven chimeric proteins identified in this study within our dataset, underlining their importance for the establishment of the ochrophyte plastid (Figure 6, panel A) (Méheust et al, 2016).
10.7554/eLife.23717.031Figure 6.Origins of chimeric proteins in the ochrophyte plastid.(Panel A ) tabulates eight ancestral HPPGs containing domains of cyanobacterial and non-cyanobacterial origin, as previously identified (Méheust et al, 2016) that were inherited by the ochrophyte plastid, and two chimeric ancestral HPPGs which are probably of specific ochrophyte origin.
…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, the chimeric origins of the ochrophyte plastid might have enabled the creation of syncretic proteins not found in the endosymbiont or host ancestors. We identified orthologues of seven chimeric proteins identified in this study within our dataset, underlining their importance for the establishment of the ochrophyte plastid (Figure 6, panel A) (Méheust et al, 2016).
10.7554/eLife.23717.031Figure 6.Origins of chimeric proteins in the ochrophyte plastid.(Panel A ) tabulates eight ancestral HPPGs containing domains of cyanobacterial and non-cyanobacterial origin, as previously identified (Méheust et al, 2016) that were inherited by the ochrophyte plastid, and two chimeric ancestral HPPGs which are probably of specific ochrophyte origin.
…”
Section: Resultsmentioning
confidence: 86%
“…We identified orthologues of seven chimeric proteins identified in this study within our dataset, underlining their importance for the establishment of the ochrophyte plastid (Figure 6, panel A) (Méheust et al, 2016).
10.7554/eLife.23717.031Figure 6.Origins of chimeric proteins in the ochrophyte plastid.(Panel A ) tabulates eight ancestral HPPGs containing domains of cyanobacterial and non-cyanobacterial origin, as previously identified (Méheust et al, 2016) that were inherited by the ochrophyte plastid, and two chimeric ancestral HPPGs which are probably of specific ochrophyte origin. (Panel B ) shows a complete tabulated list of all ancestral HPPGs (listed by identifier, with the predicted function given in brackets) in which at least one chimerism event between domains of red algal, green algal, aplastidic stramenopile, other eukaryotic, and prokaryotic origin was detected.
…”
Section: Resultsmentioning
confidence: 86%
“…As with mitochondria, conversion of the endosymbiotic bacterium into an organelle involved considerable DNA transfer to the nuclear genome. A number of nuclear‐encoded proteins important for plastid function have sequence signatures indicating cyanobacterial contributions to their evolution . In the Arabidopsis embryophyte nuclear genome, for example, it was found that ∼18% of the nuclear protein‐coding sequences came from Cyanobacteria …”
Section: Multiple Cell Fusions In the Evolution Of Photosynthetic Eukmentioning
confidence: 99%
“…Furthermore, dinoflagellates have been shown to 'recycle' genetic material to regulate their plastid photosynthetic machinery (Méheust, Zelzion, Bhattacharya, Lopez, & Bapteste, 2016). In the case of the saxitoxin biosynthesis pathway, it's possible that genes from a HGT event between a cyanobacterium and a dinoflagellate are now being used not only to produce saxitoxin and its derivatives, but also may be used in other pathways.…”
Section: Saxitoxin Biosynthesis Pathwaymentioning
confidence: 99%
“…Furthermore, endosymbiosis may be an even greater driver of HGT in dinoflagellates since they have been shown to incorporate an unusually high proportion of plastid genes to their nucleus, more so than many other eukaryotes (Archibald, 2009;Dorrell & Howe, 2015). Dinoflagellates also 'recycle' genetic material to regulate their plastid photosynthetic machinery from multiple sources which sometimes results in the fusion of domains from different organisms into chimeric sequences (Méheust et al, 2016). They also recycle genes for use in different pathways, resulting in at least one documented example of a hybrid metabolic pathway with components from different evolutionary origins (Bentlage, Rogers, Bachvaroff, & Delwiche, 2016).…”
Section: Introductionmentioning
confidence: 99%